Molecular and Bacteriological Study of Enterococcus faecalis Isolated from Different Clinical Sources - Khalil H. Khdir; Khadija kh. Mustafa (Zanco Journal of Pure and Applied Sciences, 2020)
Enterococci are Gram-positive bacteria that cause serious nosocomial infections, including urinary tract, bloodstream infections and endocarditis. During the period of September 2018 to February 2019, forty four isolates of E. faecalis were isolated from 826 clinical specimens including; 35(5.07%) isolates of E. faecalis from urine, 7(7.60%) isolates from high vaginal swab and 2(8.69%) isolates from blood patients in different hospitals. All isolates that described above were identified depending on cultural criteria, morphological criteria, biochemical tests and further confirmed by Vitek 2 compact systems. The results of eleven antimicrobial against obtained isolates revealed that 100% of E. faecalis were resistant to cefotaxime, vancomycin, amoxicillin and erythromycin. While, it were 100% sensitive to doxycycline, imipenem, and nitrofurantion. Whereas, most isolates were differ in their susceptibility to amikacin, gentamycin, tetracycline and azithromycin. On the other hand, the results of biofilm found that 13.63% of isolates were produce strong biofilm, 54.54% were produce moderate biofilm and 31.81% were produce weak biofilm. The results of molecular analysis by using PCR showed that isolated E. faecalis were carried 97.72%, 90.90%, 63.63% of ebpR, asa1, esp genes respectively.